Proposal for soybean genotype selection based on the agronomic and environmental resilience index - Donadel Port, Eduarda; Carvalho, Ivan Ricardo; Colet, Christiane de Fátima; Gonzalez da Silva, José Antonio; Vieira Loro, Murilo; Adorian Bandeira, Willyan Júnior; Piesanti Sangiovo, Jaqueline; Pradebon, Leonardo Cesar (Pesquisa Agropecuaria Brasileira, 2026)
The objective of this work was to propose a selection index based on the agronomic and environmental resilience of soybean. The experiment was carried out at the research farm of Universidade Regional do Noroeste do Estado do Rio Grande do Sul. The user experimental design was that of augmented blocks with interspersed controls, arranged in three replicates. The regular treatments corresponded to 89 F8 lineages (99.218% homozygosity), and the common treatments were represented by four commercial controls (BRS 284, BMX Valente 6968 RSF RR, BMX Raio 50I52 RSF IPRO, and M 5710 I2X45). The following agronomic variables were measured based on five plants per experimental unit: number of seeds per plant and seed weight per plant. The agronomic and environmental resilience index (GSIR∆) was proposed in order to combine the attributes of seed number and weight with meteorological data. Selection based on the GSIR∆ allows selecting 13 lineages (122F8, 176F8, 165F8, 232F8, 109F8, 99F8, 166F8, 93F8, 154F8, 85F8, 121F8, 152F8 and 169F8) with a high agronomic potential for productivity and resilience to abiotic stresses, such as high temperatures and low precipitation volumes.